PENGARUH KUALITAS PELAYANAN KOPERASI TERHADAP KEPUASAN ANGGOTA KOPERASI SERBA USAHA (KSU) MIKAT AL KHIDMAH KECAMATAN KUTOARJO - AlaDarojah (STIE Rajawali Purworejo, 2024)
This study examines the impact of service quality on member satisfaction at KSU Mikat Al Khidmah, Kutoarjo District. A sample of 50 members was randomly selected from a population of 456. Data were collected via a Likert-scale questionnaire tested for validity and reliability. Data were analyzed using simple linear regression, determination analysis, and t-test. Results show a strong relationship between service quality and member satisfaction, with a correlation value of 0.732. Linear regression indicates that even with zero service quality, member satisfaction remains positive at 4.047. Service quality influences member satisfaction by 53.6%. The t-test confirms an impact, with a t-value of 7.453 exceeding the t-table value of 1.677. Improving service quality at KSU Mikat Al Khidmah is recommended to enhance member satisfaction and welfare, including through mobile app or interactive website development and accessible feedback systems.